Transcranial direct current stimulation enhances the efficacy of wearable transcutaneous electrical nerve stimulation for mild knee osteoarthritis in the middle-aged person: a randomized controlled trial - Chun-Ya Xia; Hao-Zhi Niu; Xin-Wen Zhang; Si-Yan Cai; Ying-Jie Fan; Tian-Pei Xie; Peng-Xia Dong; Xiao-Tong Zu; Ze-Lin Su; Xing-Sheng Lu; Yong-Gang Hao; Min Su (BMC Musculoskeletal Disorders)
Abstract Objective To evaluate the efficacy of wearable transcutaneous electrical nerve stimulation (TENS) combined with transcranial direct current stimulation (tDCS) in the middle-aged person with mild knee osteoarthritis (KOA). Design Double-blind, randomized clinical trial. Setting A general hospital. Subjects Participants aged 60–70 with mild KOA (Kellgren–Lawrence grade 1–2). Interventions The experimental group received TENS + tDCS, and the control group received TENS + sham tDCS for four weeks from Monday through Friday. Main measures The primary outcome was Brief Pain Inventory (BPI). The secondary outcomes included participants’ Visual Analog Scale (VAS), step length, cadence, 6-minute walking test (6MWT), active knee range of motion (ROM), and quadriceps strength. The indexes were assessed one week before treatment (T0), two weeks after treatment commencement (T1), four weeks after treatment commencement (T2), one month after treatment cessation (T3), and two months after treatment cessation (T4). Results A total of 110 participants (55 per group) completed the intervention and follow-up. Repeated-measures ANOVA indicated that tDCS significantly improved the efficacy of TENS in alleviating pain and enhancing walking ability among patients with mild KOA. Statistically significant differences in BPI scores were observed between the experimental and control groups at T1 (2.16 vs. 2.45, P = 0.038), T2 (1.17 vs. 1.73, P < 0.001), and T3 (2.17 vs. 2.41, P = 0.021). However, no significant difference was detected at T4 (2.50 vs. 2.63, P = 0.293). Conclusion The four-week combined intervention demonstrated that tDCS potentiated the therapeutic efficacy of TENS in managing mild KOA. The combined protocol exhibited superiority over TENS monotherapy, with sustained benefits observed up to one-month post-intervention. Trial registration This research has been registered in chictr.org.cn (registration number: ChiCTR2200064735) on 15 October 2022, https://www.chictr.org.cn/showproj.html?proj=182561 .